Menilai Succession Management Sebagai Sistem Baru dalam Perencanaan Sumber Daya Manusia - Noor Afiffa Ika Mariliani (Sinergi: Kajian Bisnis dan Manajemen, 2005)
Organizations need to form the appropriate human resource management plan¬ning to meet the challenge of the dynamic, competitive, and global organizational environ¬ment. Human resource management planning is the process by which management determines how the organization should move from its current position to the desired position in the fu¬ture competitive realities. Through HR planning, management strives to have the right number and the right kinds of person, at the right places and time for the benefits of both organization and the people. However, the traditional succession planning is not enough and need to be modified. Rather than focusing on the right men at the right time, organizations need to de¬velop strong leadership teams for strategic tasks. Future competitive success requires not only different leadership success model, but also succession system that is feedback-rich, highly flexible, transparent, and that accelerates the development of leaders for the next generation. Succession management system allows the corporate leadership to build a more dynamic process easier to integrate with the firm’s strategic initiatives.Keywords:     Human Resource Planning, Succession Planning, Succession Management, Competitive  Environment.